Nitrogen rate, timing, and fungicide interactions for corn production and assessment of plant nutrient analysis - Stammer, Andrew John (Kansas State University, 2023)
Ensuring appropriate crop nutrition is essential to optimize productivity and minimize environmental impact. To achieve this, we assessed the effect of nitrogen (N) application techniques during the early vegetative and early reproductive stages of corn (Zea maize) and interactions with the use of fungicides. New corn hybrids' yield potential and stay-green characteristics may benefit from late N fertilizer applications. Late N applications can also include foliar N applications in combination with management practices such as late fungicide applications. This combination of late N and fungicide may benefit corn and contribute to “stay green” conditions until much later in the grain filling period, contributing to yield. Our study evaluating interactions of N rate, timing, and fungicide found that delayed N fertilizer application of a significant portion of the total N fertilizer to vegetative stages may be too late in some cases and result in yield penalty. Late N application was beneficial, but only when initial fertilizer rates were sufficient to meet corn growth and development needs until the reproductive stages. The overall response to fungicides was significant for specific site years, showing likely driven by given conditions favoring the development of the disease. Another study compared a range of N fertilizer rates and timings for corn. The experiment was conducted with a zero N control and a range of five N rates. The Kansas State University recommendation was used for each study site; plus and minus increments of 28 and 56 kg N/ha were established, either all at planting to V4 or 60% at planting and 40% at the VT growth stage. The Kansas State University nitrogen recommendations were not low enough to reduce yield, even at high-yielding sites. Therefore, the site-specific recommendation is likely at least 56 kg N/ha over the optimum agronomic rate for a specific location, either pre-plant or split-applied. Analysis of plant nutrient content is a common diagnostic tool to assess plant nutritional status. We evaluated different methods and determined that dry ashing and nitric perchloric digestions gave similar results and repeatability for several nutrients. However, a new closed tube method had a lower recovery, likely due to lower digestion temperatures and less complete reaction than the established methods and other similar methods that have proven successful.
Keywords: Corn; Late nitrogen; Nitrogen; Fungicide; Plant tissue analysis; Foliar fertilizer